Предмет: Алгебра,
автор: Ученикученик1
Решите уравнение
х^2 (х+1)-(х+2)(2х-3)=х^2 (х-1)
Ответы
Автор ответа:
0
+x2(x+1)-(x+2)(2x-3)=x2(x-1)
+1x2(1x+1)-(1x+2)(2x-3)=1x2(1x-1)
+1x2(1x+1)-(1x+2)(2x-3)=1x2(1x-1)
(1x3+1x2)-(2x2-3x+4x-6)=(1x3-1x2)
1x3+1x2-2x2+3x-4x+6=1x3-1x2
1x3+1x2-2x2+3x-4x+6=1x3-1x2
1x3-1x2-1x+6=1x3-1x2
-1x=-6
-1x=-6
-1x=-6
1x=6
+1x2(1x+1)-(1x+2)(2x-3)=1x2(1x-1)
+1x2(1x+1)-(1x+2)(2x-3)=1x2(1x-1)
(1x3+1x2)-(2x2-3x+4x-6)=(1x3-1x2)
1x3+1x2-2x2+3x-4x+6=1x3-1x2
1x3+1x2-2x2+3x-4x+6=1x3-1x2
1x3-1x2-1x+6=1x3-1x2
-1x=-6
-1x=-6
-1x=-6
1x=6
Похожие вопросы
Предмет: Математика,
автор: kotelnikovadasha
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: aldanbajbosyn
Предмет: История,
автор: Vika12508
Предмет: Алгебра,
автор: MikyNagane